Finite Element Method - Its Basis and Fundamentals (7th Edition) - Zienkiewicz, O. C.; Taylor, R. L.; Zhu, J. Z. (Elsevier, 2013)
This book offers a complete introduction to the basis of the finite element method, covering fundamental theory and worked examples in the detail required for readers to apply the knowledge to their own engineering problems and understand more advanced applications. This edition sees a significant rearrangement of the book's content to enable clearer development of the finite element method, with major new chapters and sections added to cover: Weak forms; Variational forms; Multi-dimensional field problems; Automatic mesh generation; Plate bending and shells; Developments in meshless techniques. Focusing on the core knowledge, mathematical and analytical tools needed for successful application, this book is the authoritative resource of choice for graduate level students, researchers and professional engineers involved in finite element-based engineering analysis.